Pengaruh Kombinasi Porasi dan Pupuk Hayati (M-Bio) Terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frustescens L.) Varietas Bara - Priyadi, Rudi; Juhaeni, Ade Hilman; Taufiq, Hilda (AGRICOLA, 2020)
Porasi is a fermented organic manure which can provide nutrients for plants in a short time. Theapplication of biological fertilizer (M-Bio) to the soil provides good nutrient fixing microbes for thesoil and plants. This research aimed to determine the effect of a combination of porasi and biologicalfertilizer (M-Bio) on the cultivation of cayenne pepper plants. Research using Randomized BlockDesign (RBD) one factor consisting of five treatments repeated five times. The combination oftreatments used A (without porasi 0 t/ha and without M-Bio), B (Porasi 8 t/ha + Biological fertilizers(M- Bio) 1,5 ml/L), C (Porasi 12 t/ha + Biological fertilizers (M-Bio) 3 ml/L), D (Porasi 16 t/ha +Biological fertilizers (M-Bio) 4,5 ml/L), and E (Porasi 20 t/ha + Biological fertilizers (M- Bio) 6 ml/L).The results showed that the dose combination of porasi 20 t/ha + biological fertilizer (M-Bio) 6 ml/Lobtained growth and good results in the cultivation of cayenne pepper (Capsicum frustescens L.)varieties of Bara